Silent witness - Patterson, Richard North (Ballantine Books, 1996)
Patterson's most stunning novel to date offers a powerful portrayal of the complexities of male friendship, of the darkest recesses of love, and of the ways in which the past stakes it claim upon the present. When attorney Tony Lord returns to his hometown to defend his former high school best friend who's been accused of murder, Tony is plunged into the unfinished business of his past.